A CAD methodology for optimizing transistor current and sizing in analog CMOS design. - Binkley, D.M (IEEE Transactions on computer-aided design of integrated circuits and systems)
A computer-aided design (CAD) methodology for optimizing MOS transistor current and sizing is presented where drain current ID, inversion level (represented by inversion coefficient IC), and channel length L are selected as three independent degrees of design freedom resulting in an optimized selection of channel width for layout. At a given drain current ID in saturation, a selected MOS inversion coefficient IC and channel length L define a point on an operating plane illustrating dramatic tradeoffs in circuit performance. Operation in the region of low inversion coefficient IC and long channel length L results in optimal DC gain and matching compared to the region of high inversion coefficient IC and short channel length L where bandwidth is optimal. A design methodology is presented here to enable optimum design choices throughout the continuum of inversion level IC (weak, moderate, or strong inversion) and available channel length L. The methodology is implemented in a prototype CAD system where a graphical view permits the designer to explore optimum tradeoffs against preset goals for circuit transconductance gm, output conductance gds, drain-source saturation voltage, gain, bandwidth, white and flicker noise, and DC matching for a 0.5-μm CMOS process. The design methodology can be readily extended to deeper submicron MOS processes through linkage to the EKV or BSIM3 MOS models or custom model equations.